Towards an alignment of activities, aspirations and stakeholders for responsible innovation. Issue 3 (1st September 2016) - Foley, Rider W.; Bernstein, Michael J.; Wiek, Arnim
ABSTRACT: Governance of technological innovation remains challenged by the dilemma of control. Two divergent responses seek to meet this challenge. The first regulates negative impacts once evidence is gathered. The second precludes dissemination of technologies until enough is known about outcomes. Recognizing limitations of each response, scholars are increasingly exploring responsible innovation (RI), a concept that revolves around dimensions of anticipation, reflexivity, inclusion, and responsiveness. At present, current conceptualizations of RI do not address questions of "to what end?" or "how to innovate responsibly?" This paper informs RI with sustainability principles and proposes an alignment of activities, aspirations, and stakeholders with previously defined dimensions for RI. A case study on nanotechnology innovation illustrates the applicability of this framework for assessing innovation governance. The proffered idea of alignment, buttressed by insights from sustainability and adaptive management, is intended to support the practice of RI by government agencies, industry, and diverse stakeholders.